A three-dimensional requirements elicitation and management decision-making scheme for the development of new software components - Andreou, Andreas S.; Zographos, Andreas C.; Papadopoulos, George A. (My University, 2003)
Requirements analysis and general management issues within the development process of new software components are addressed in this paper, focusing on factors that result from requirements elictation and significantly affect management decisions and development activities. A new methodology performing a certain form of requirements identification and collection prior to developing new software components is proposed and demonstrated, the essence of which lays on a three-entity model that describes the relationship between different types of component stakeholders: Developers, reusers and end-users. The model is supported by a set of critical factors analysed in the context of three main directions that orient the production of a new component, that is, the generality of the services offered, the management approach and the characteristics of the targeted market. The investigation of the three directions produces critical success factors that are closely connected and interdependent. Further analysis of the significance of each factor according to the priorities set by component developers can provide a detail picture of potential management implications during the development process and more importantly can support management decisions related to if and how development should proceed.
Keywords: Management decision-making; Requirements elictation; Reusability; Software components development